The culture of "silent sexuality" amongst the Shambala of Tanzania : towards an intercultural approach in the pastoral ministry - Shemsanga, Eberhardt Ngugi (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.